2014
DOI: 10.3393/ac.2014.30.6.266
|View full text |Cite
|
Sign up to set email alerts
|

Role of Peritoneal Lavage Cytology and Prediction of Prognosis and Peritoneal Recurrence After Curative Surgery for Colorectal Cancer

Abstract: PurposeIn colorectal cancer, the role of detecting free malignant cells from peritoneal lavage is currently unclear. In this study, we investigated the positive rate of free malignant cells in peritoneal lavage fluid and their predictive value for prognosis and peritoneal recurrence after a curative resection.MethodsFrom October 2009 to December 2011, in a prospective manner, we performed cytologic examinations of peritoneal lavage fluid obtained just after the abdominal incision from 145 patients who underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Multicenter studies reported that IPCCs are associated with peritoneal recurrence and worse survival 3,7 . However, other authors argue for the prognostic role of free IPCCs on survival and rejected its predictive significance for peritoneal recurrence after a curative resection 10,12 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Multicenter studies reported that IPCCs are associated with peritoneal recurrence and worse survival 3,7 . However, other authors argue for the prognostic role of free IPCCs on survival and rejected its predictive significance for peritoneal recurrence after a curative resection 10,12 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite the current debate of the actual significance of positive peritoneal fluid cytology, some authors still considered it evidence of the local aggressiveness of the disease during surgery. It may help in making the decision of whether to apply any of the previous treatment strategies immediately after resection of the tumor 7,17 . Either side of this argument should be supported by multi‐institutional studies to determine the prevalence of IPCC and to evaluate the real prognostic impact of peritoneal lavage cytology.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among gastrointestinal malignancies, the significance of peritoneal cytology has been extensively studied in gastric cancer. The existence of free cancer cells at intraoperative peritoneal lavage has been reported to be one of the most accurate prognostic factors for gastric cancer and is now classified as Stage IV [ 3 , 4 ]. Besides gastric cancer, the examination of peritoneal free cancer cell is an important staging step in pancreatic, ovarian and endometrial cancer [ 5 ]…”
mentioning
confidence: 99%